Characteristics of the roles of mothers of children with intellectual disabilities as a basis for their individual therapy - MARCIN BIALAS (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: ‪Women enjoy a variety of social roles during their lives. Among the commonly known ones, which include e.g. the roles of wives and mothers, there are also those that radically change the scenario of one's past life. These include the role of mothers of children with intellectual disabilities. After all, the hardships associated with caring for them and with their upbringing, influence their mothers' perception of the world, change the existing family and professional social relations, determine the choice of values, and limit or block the goals set to date. It seemed interesting to the author of the study to recognise the roles of mothers of children with intellectual disabilities. Material and methods: ‪Their categorisation revealing the nature of a given role was possible owing to the conducted research. It was attended by 104 mothers of children with intellectual disabilities who answered a series of questions included in the interview questionnaires. A hermeneutical analysis of their answers made it possible to describe a given role in detail. Among these four can be distinguished which are conventionally defined as: «REBEL», «RATIONALIST», «SHAM» and «RESOURCEFUL». Results: ‪These roles are fundamentally different from each other, indicating the traits that characterise mothers bringing up children with intellectual disabilities. Identifying oneself with one of them may show both the desired features of the role played and indicate the destructive elements which negatively determine the course of their previous lives. Conclusions: ‪This is the basis for personalised therapy dedicated to mothers of children with intellectual disabilities.